Planos discursivos em texto bíblico: o fundo narrativo nas versões Almeida Revista e Corrigida (ARC) e Nova Versão Internacional (NVI) - Livia Miranda de Lima Santos (2017)
This work aimed to comparatively analyze two versions of a biblical narrative story in the Portuguese language. In our analysis, we based on the studies of Hopper (1979), Reinhart (1984), and Azevedo (1995) on Foregrounding and Backgrounding in narratives. In order to perceive the existence of significant differences in the selection of sentences from Narrative Foreground and Narrative Background while comparing two versions of the same narrated story, we followed three questions that inspired this research. It was questioned if two versions of the same narrative would preserve the same amount of sentence selection, clause units, Foreground and Background occurrences, which our analysis revealed that did occur. The second questioning was to determine if the selection of the narrative Backgrounding between the analyzed versions would also be different, and this work demonstrated that, numerically, there was not significative difference between both translations. In addition, one of the versions attested verbs much more diversified in Verb Tense and Aspect than the other. Our research also attested that the sentences of a narrative tend to be structured in Realis Mode. The last questioning of this work had to do with the presence or lack of difference in terms of the levels of Backgrounding, proposed by Silveira (1990) between the sentences of Narrative Background of the two versions accounted. Again, the versions presented differences when analyzed. The analysis of this work prove that the same narrative may encompass different structures of Narrative Background. It was also observed that the textual legibility of a narrative seems to be linked to a more frequent use of the verbal mode Realis and Background clauses in deeper levels, which focus on working as auxiliaries to the reader's comprehension of the story told. Lastly, the results of this paper are in compliance with Gestalt Theory - the more we are able to distinguish discursive plans, the more we observe the picture or story that is being narrated.